Natural MHD convection for an impulsively started infinite vertical plate with diffusion‐thermo effect, induced magnetic field, and ramped wall temperature and concentration. Issue 2 (16th November 2021) - Ahmed, Nazibuddin; Gohain, Dipunja
Abstract: The major motive of the current investigation is to analyze an exact solution for an unsteady magnetohydrodynamics natural convective flow of a viscous incompressible electrically conducting non‐gray optically thick fluid past an impulsively started infinite vertical plate with ramped wall temperature and concentration in the presence of radiation, diffusion‐thermo effect, and induced magnetic field. Laplace transform method is used to acquire the specific solutions of the dimensionless domain equations. The impact of various physical parameters on fluid velocities, temperature, concentration, and moreover on the rate of heat transfer, mass transfer, and skin friction at the wall are shown graphically. It is also found that the Dufour effect causes an increase in fluid velocity as well as temperature. The ramped condition influences the rise in Nusselt number.